2015
DOI: 10.1155/2015/652738
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Immunity and Inflammation by the Mineralocorticoid Receptor and Aldosterone

Abstract: The mineralocorticoid receptor (MR) is a ligand dependent transcription factor. MR has been traditionally associated with the control of water and electrolyte homeostasis in order to keep blood pressure through aldosterone activation. However, there is growing evidence indicating that MR expression is not restricted to vascular and renal tissues, as it can be also expressed by cells of the immune system, where it responds to stimulation or antagonism, controlling immune cell function. On the other hand, aldost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 146 publications
(179 reference statements)
0
24
0
4
Order By: Relevance
“…Surprisingly, we also revealed that ApoE-KO mice treated with aldosterone display instead an increase of peripheral Tregs, presumably due to their recruitment at the plaque region to suppress the inflammation promoted by aldosterone. It is well-known, indeed, that this hormone is associated with vascular infiltration of immune cells, reactive oxidative stress, and pro-inflammatory cytokine production (59).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we also revealed that ApoE-KO mice treated with aldosterone display instead an increase of peripheral Tregs, presumably due to their recruitment at the plaque region to suppress the inflammation promoted by aldosterone. It is well-known, indeed, that this hormone is associated with vascular infiltration of immune cells, reactive oxidative stress, and pro-inflammatory cytokine production (59).…”
Section: Discussionmentioning
confidence: 99%
“…MR blockade with eplerenone (an MR antagonist) has been demonstrated to rectify the reductions in the mRNA expressions of adiponectin and PPARγ that are induced by aldosterone in adipocytes. However, contrasting results have demonstrated that pretreatment with eplerenone does not affect the reduction in the adiponectin mRNA level that is induced by aldosterone [15,16].…”
Section: Introductionmentioning
confidence: 94%
“…MR is also expressed by cells of the immune system and may modulate immune cell function. Aldosterone also has been associated with proinfl ammatory immune effects, such as the release of proinfl ammatory cytokines, generating oxidative stress and inducing fi brosis [ 88 ] . MR can regulate NF-κβ pathway(s) through activation of serum-and glucocorticoid-inducible protein kinase-1 (SGK1) [ 98 ] .…”
Section: Discussionmentioning
confidence: 99%